The invention of the tourist destination - Rémy Knafou (Via@)
This paper first analyses the development of the invention of the tourist destination from a dual perspective, namely research on tourist resorts in the Alps and the evolution of ideas related to the study of tourism during the 1970s and 1980s. It then goes on to discuss the difficulties in identifying the reception of this concept. Finally, it examines the relationship between the invention of tourism and the concept of “moment in place”.